Ikatan Emosional Asertif dalam Narasi Film Ngeri-Ngeri Sedap dari Perspektif Trompenaars - Hermanto, Febe Oriana; Marta, Rustono Farady; Panggabean, Hana; Chinmi, Maichel (Fakultas Ilmu Komunikasi Universitas Tarumanagara, 2023)
Not many media products are able to reveal the other side of a particular ethnic identity and entity. However, the Horrific-Ngeri Sedap film manages to present the uniqueness of one of the tribes in Indonesia, namely the Batak tribe. The film directed by Dion Rajagukguk won seven awards at the 2022 Indonesian Journalist Film Festival (FFWI). Through this film, people are taught about the importance of maintaining emotional bonds in a family for the sake of the integrity of relationships. This study aims to see the role of the dimension of relational expression and assertive communication style using Tzvetan Todorov's narrative analysis method. The results of this study indicate that the affective and collectivism cultural dimensions dominate the Ngeri-Ngeri Sedap films which are at the same time cultural characteristics inherent in the lives of Indonesian people. In addition, the assertive communication style is still highlighted in this film even though the main character almost always uses an aggressive communication style. Tidak banyak produk media yang mampu membeberkan sisi lain dari identitas dan entitas suku tertentu. Namun Film Ngeri-Ngeri Sedap berhasil menyajikan keunikan dari salah satu suku di Indonesia, yaitu suku Batak. Film yang digarap oleh Dion Rajagukguk ini berhasil memborong tujuh penghargaan di Festival Film Wartawan Indonesia (FFWI) 2022. Melalui film ini, masyarakat diajarkan tentang pentingnya merawat ikatan emosional dalam sebuah keluarga demi keutuhan relasi. Penelitian ini bertujuan untuk melihat adanya peranan dimensi ekspresi relasi serta gaya komunikasi asertif dengan metode analisis naratif Tzvetan Todorov. Hasil penelitian ini menunjukkan bahwa dimensi budaya afektif dan kolektivisme mendominasi film Ngeri-Ngeri Sedap yang sekaligus merupakan ciri khas budaya yang melekat pada kehidupan masyarakat Indonesia. Selain itu, gaya komunikasi asertif tetap ditonjolkan dalam film ini sekalipun tokoh utama hampir selalu menggunakan gaya komunikasi agresif